Mosses of Cockburn Island plateau, Antarctica - Cottet, Agustina Celeste (2024)
Located east of the Antarctic Peninsula, Cockburn Island is a small island in the James Ross Archipelago. Studies of mosses on the island are scarce. The oldest studies date from the first half of the nineteenth century to the most recent in 1993. The number of records of mosses is very small due to the difficulty of accessing the area. Here, we report an updated composition of the moss flora of the plateau, in which four new records have been found: Bryoerythrophyllum antarcticum, Ceratodon purpureus, Pohlia wilsonii and Schistidium lewis-smithii. The occurrence of these species on the plateau shows that the ranges of these species have expanded from the Antarctic Peninsula to the east. This collection highlights the need for further research into the dynamics of moss flora in the context of climate change.